Mapping Groundwater Potential Zones in Parts of Southwestern Nigeria: An Integrated Approach - Mumeen Adebayo, Yusuf; Kola-Aderoju, Abdulmalik Olayinka; Olaleye, Ifeoluwa Mathilda; Bakare, Ussein Taiwo; Omotoso, Oladele Ajiboro; Olojoku, Kehinde Ibrahim; Oyeleke, Tolulope Ayobi; Abiye, Tamiru Alemayehu; Alao, Joseph Omeiza; Yusuf, Olajumoke Bukola; Akogun, Majeed (Journal of Sustainable Natural Resources, 2025)
Groundwater is undoubtedly the most abundant source of freshwater on Earth. However, groundwater assessment and exploration are multi-tasking particularly in the basement complex terrain due to uneven distribution of this resource within the subsurface aided by variations in hydrogeological factors. To overcome these tasks, the integrated approach based on advanced applications of Geographic Information System (GIS), Remote Sensing (RS), Analytic Hierarchy Process (AHP), and Vertical Electrical Resistivity (VES) serves as a useful and efficient tool for studying the development and management of the water resources in southern parts of Akure. Akure south region, comprising a hard rock terrain, is situated in the water grappled zone of southwest, Nigeria. The groundwater potential was evaluated based on eight relevant and effective factors: slope, lineament density, drainage density, geology, aquifer thickness, resistivity, hydraulic conductivity, and transmissivity. The final GWPZ map is categorized into three potentiality zones following overlay analysis of the thematic layers in the ArcGIS 10.8 environment: the poor zone (which makes up the majority of the area with 57%), the intermediate zone (35%), and the good zone (8%). After CR was used to validate the final Groundwater Potential Zones (GWPZ) map created by combining all the theme layers, it was found that AHP was a useful method (CR accuracy = 0.08 or 8%) for identifying possible groundwater zones in the research area. The research demonstrated that a multi-technique approach is the most reliable and effective method for accurately assessing groundwater potential.